Nilai Kesundaan Cageur (sehat akal), Bageur (baik) dan Bener (benar) sebagai Kearifan Lokal Dalam Perspektif Konsep Hukum Perdata di Indonesia - delila kania (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2021)
Indonesian struggle since the pioneering Indonesian nationalist movement, the youth play an active role as the spearhead in delivering the nation of Indonesia is an independent, unified and sovereign. Youth has a function and a strategic role so that the need to develop the potential and its role through awareness, empowerment, and development as part of national development. Indonesia is a country with a large number of youth so that needs guidance. Youth is one of the appropriate container in building and preparing the younger generation and printing leadership cadres of our nation's future. Through various activities and programs that support employment and contribute positively to the nation's youth. including; (1) Routine Meeting, (2) Sports, (3) Spirituality, (4) Education and Training. All these activities are packed in order to print the character of the young generation intelligent leadership in thinking, strong in the physical, and noble.